My Child Doesn’t Need to be Vaccinated Because we Lead a Healthy Lifestyle: Compensatory Health Beliefs Predicting Intentions and Reported Child Vaccination - Neter, Efrat; Levi, Bat-El; Miller, Sharon (Archives of Community Medicine and Public Health, 2015)
Background: In the past two decades negative attitudes towards vaccination has surfaced among parents. These concerns are related to safety, adverse effects, lifestyle and religious issues. The present study focuses on compensatory health beliefs (CHB), the beliefs that the adverse consequences of one health behavior are compensated by another health behavior, and examines whether CHB predicts behavior and mediates the association between the intention to vaccinate one’s children and vaccination behavior. Methods: Parents (n=90) to children up to 6 years old filled an online questionnaire taping intentions and behaviors to vaccinate, self-efficacy to vaccinate, compensatory health beliefs related to vaccination and lifestyle. Results: A significant negative association was found between CHB and intention to vaccinate and vaccination behavior (r=-0.69, p<.01), and a non-significant positive association was found between CHB and lifestyle. CHB partially mediated the association between intention and vaccination behavior (ZSobel=2.97, p<.01). Conclusions: Future campaigns to increase vaccination should address CHB directly.